2010
DOI: 10.3346/jkms.2010.25.4.613
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Serotonin Transporter Function and Heart Rate Variability in Patients with Panic Disorder

Abstract: Many studies showed abnormal serotonin transporter (5-HTT) function and heart rate variability (HRV) in panic disorder patients. The present study investigated the relationship between HRV power spectral analysis findings and platelet serotonin uptake in panic disorder patients. Short-term HRV over 5 min and platelet serotonin transporter uptake parameters (Vmax and Km) were measured both in 45 patients with panic disorder and in 30 age-matched normal healthy control subjects. Low frequency power (LF) normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“… 30 In one study, platelet 5-HT uptake maximal velocity ( V max) and its associated affinity constant ( K m ) were found to be lower in PD patients than in normal control subjects. 41 In this study, Kang et al reported that patients with PD showed abnormalities in platelet 5-HTT function; furthermore, they found that after 12 weeks of paroxetine treatment, the K m values of platelet serotonin transporters increased in parallel to clinical improvement. They speculated that impaired 5-HTT function might be related to the dysregulation of the autonomic nervous system in PD.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“… 30 In one study, platelet 5-HT uptake maximal velocity ( V max) and its associated affinity constant ( K m ) were found to be lower in PD patients than in normal control subjects. 41 In this study, Kang et al reported that patients with PD showed abnormalities in platelet 5-HTT function; furthermore, they found that after 12 weeks of paroxetine treatment, the K m values of platelet serotonin transporters increased in parallel to clinical improvement. They speculated that impaired 5-HTT function might be related to the dysregulation of the autonomic nervous system in PD.…”
Section: Discussionmentioning
confidence: 65%
“…They speculated that impaired 5-HTT function might be related to the dysregulation of the autonomic nervous system in PD. 41 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent Korean study, there were no significant differences in time‐domain indices of HRV between PD patients and controls; however, frequency‐domain analysis of HRV revealed that LF normalized unit (nu) and LF/HF ratio were significantly higher, whereas HF and HF nu were lower in PD patients than in controls (Kang et al ., ). Similarly, Alvarenga et al .…”
Section: Discussionmentioning
confidence: 97%
“…(i) Kang et al . () suggested that impaired 5‐HTT function, as measured by platelet 5‐HTT uptake, was closely related to ANS dysregulation in PD. (ii) Tucker et al .…”
Section: Discussionmentioning
confidence: 99%
“…Based on measures of CAM, the level of anxiety is expected to correlate inversely with HF and proportionally with LF and LF/HF [45]. Failure of our results to demonstrate the expected trend between TMAS and measures of CAM may partly be explained by the relatively low anxiety levels in the studied groups.…”
Section: Discussionmentioning
confidence: 66%